PSYCHOPHYSIOLOGY OF SILENCE (Scientific journal of the Fergana State University, 2025)
The article examines the issue of psychophysiological condition on the example of the stories of the writer Nabi Jalaluddin. In it, the theoretical foundations of psychophysiological tools, which are being studied with interest by literary scholars today, are analyzed